2011
DOI: 10.5012/bkcs.2011.32.6.1925
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Chaperone Activity of DnaK from Cold-adapted Bacteria, KOPRI22215

Abstract: Psychrophilic bacteria have acquired cold-resistance in order to protect themselves against freezing temperatures, which would otherwise be lethal. DnaK/DnaJ/GrpE systems are molecular chaperones which facilitate proper folding of newly synthesized proteins. Efficient folding processes are of great importance especially in a cold environment, such as the Arctic. In order to understand the protection mechanisms of psychrophilic bacteria against cold temperatures, we have explored a genome of KOPRI22215, tentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Some interesting reports have revealed that cold-adapted chaperones such as DnaK [ 100 , 101 ] and GroEL [ 102 104 ] expressed in E. coli provide cold-resistance and improve growth of the mesophilic bacterium at low temperature, therefore highlighting the crucial involvement of chaperones in temperature adaptation of microorganisms.…”
Section: Protein Synthesis and Foldingmentioning
confidence: 99%
“…Some interesting reports have revealed that cold-adapted chaperones such as DnaK [ 100 , 101 ] and GroEL [ 102 104 ] expressed in E. coli provide cold-resistance and improve growth of the mesophilic bacterium at low temperature, therefore highlighting the crucial involvement of chaperones in temperature adaptation of microorganisms.…”
Section: Protein Synthesis and Foldingmentioning
confidence: 99%